Il museo Malmkrog. Vladimir Solov’ev al cinema - Morabito, Martina (L’ospite ingrato, 2023)
The article analyses the film Malmkrog (2020) by Puiu considering it in its intersemiotic rewriting dimension, being it a cinematic rendering of Vladimir Solovyov’s Tri razgovora o vojne, progresse i konce vsemirnoj istorii, so vključeniem kratkoj povesti ob Antichriste (1900). Beyond the study of the relationship between the film and the literary text, the environment of the house that serves as the backdrop to the (lack of) action will be investigated. The goal is to highlight the similarities between the construction of the film and of the museum, thus illuminating the most relevant aspects of intertextual dynamics. A series of visual reflections – comparisons, enlargements, cuts – in which captions become a methodological tool, ultimately allows us to place Malmkrog within a broader artistic constellation.